Creativity development through questioning activity in second language education - Yu, Xiaoling; Wang, Tzu-Yang; Yuizono, Takaya (Frontiers in Education, 2023)
Introduction Creativity is an important 21st-century skill that also plays an important role in second language use and development. This study examined the effects of creative pedagogy centered on student questioning activities for second language learners’ creativity, language proficiency, and questioning ability. Methods In the Japanese second language course, a creative activity intervention involving questioning activities was conducted for 81 university students. The students were taught how to ask higher-order questions, and they performed questioning activities and discussions about their questions after reading articles for eight lectures in 4 weeks. Results After the intervention, the quantity and quality of questions asked by participants increased and improved in the Questioning ability test. In the Creative thinking test, the three subscales of creative thinking (fluency, flexibility, and originality) improved after the intervention. In the Language proficiency test, there were also significant changes in vocabulary, grammar, and total scores after the intervention compared to before the intervention. Discussion The creative pedagogy significantly improved learners’ creativity, second language performance, and questioning ability, with a particularly positive impact on questioning ability, representing innovative thinking skills. The findings of this study not only contribute to future research on the development of creativity in second language instruction and deepen the exploration of the development of questioning ability for innovative thinking skills.